2018
DOI: 10.1021/acsabm.8b00599
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensionally N-Doped Graphene–Hydroxyapatite/Agarose as an Osteoinductive Scaffold for Enhancing Bone Regeneration

Abstract: Composite biomaterials with hierarchical structures have emerged as new approaches for bone-tissue engineering. In this study, a biomimetic, osteoconductive tricomposite scaffold made of N-doped graphene–hydroxyapatite (NG–HA) hybrids blended with an agarose (AG) matrix was prepared via a facile hydrothermal/cross-linking/freeze-drying method. The structure and composition of AG/NG–HA were examined by scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction, Fourier transform infrared,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 51 publications
(114 reference statements)
1
35
1
Order By: Relevance
“…In a later study, the authors added gelatin to the HA-coated alginate scaffold-system. In vitro results with rat bone marrow stem cells (rBMSCs) confirm the earlier results, as the HA-coated samples stimulated the proliferation and osteogenic differentiation and enhanced the protein adsorption [116]. Grafts comprised of alginate combined with a strontium-containing carbonated HA were investigated regarding their biocompatibility on MC3T3-E1 cells in vitro.…”
Section: Calcium Phosphate Hybridssupporting
confidence: 73%
See 1 more Smart Citation
“…In a later study, the authors added gelatin to the HA-coated alginate scaffold-system. In vitro results with rat bone marrow stem cells (rBMSCs) confirm the earlier results, as the HA-coated samples stimulated the proliferation and osteogenic differentiation and enhanced the protein adsorption [116]. Grafts comprised of alginate combined with a strontium-containing carbonated HA were investigated regarding their biocompatibility on MC3T3-E1 cells in vitro.…”
Section: Calcium Phosphate Hybridssupporting
confidence: 73%
“…Besides improved mechanical properties, the combination of agarose, NG and HA in the scaffold material promotes adhesion, proliferation, and osteogenic differentiation of rat MSC compared to plain agarose and composites of agarose/HA and NG/HA. These promising in vitro findings are confirmed in vivo by the curing of a rabbit femur defect within 12 weeks [116].…”
Section: Calcium Phosphate Hybridsmentioning
confidence: 62%
“…Inspired by these studies, 3D graphene foams were fabricated which maintained hMSCs viability and promoted spontaneous osteogenic differentiation without extrinsic inducers . Recently, graphene has also been used as filler in conjunction with other materials, which not only improve the mechanical strength of the composites, but also demonstrate excellent bioactivity in promoting cell proliferation and differentiation . For example, Luo et al designed a tricomposite scaffold using graphene and HA which were blended with agarose .…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…[83][84][85] For example, Luo et al designed a tricomposite scaffold using graphene and HA which were blended with agarose. [85] The as-prepared scaffold, with a hierarchical pore structure, was able to trigger osteogenic differentiation, confer good cell adhesion, enhance ALP activity, and mineralization in vitro and promote bone regeneration of critical-sized bone defect in vivo. Further, the results showed that the introduction of graphene into the hybrid scaffold was crucial to significantly improve the scaffold mechanical properties and promote the proliferation and viability of bone MSCs.…”
Section: Graphene For Bone Tissue Engineeringmentioning
confidence: 99%
“…Therefore, the use of nanohydroxyapatite (nanoHA) as a reinforcing component with osteocondutive capabilities can contribute to overcome some of these potential limitations [4,14]. NanoHA is commonly used in bone tissue regeneration due to its chemical similarity to the inorganic component of the bone matrix and its inherent characteristics such as biocompatibility, osteoinduction, osteocondutive and osteointegration [4,15,16]. Although in some studies nanoHA was already used to reinforce Alg matrixes [14,[17][18][19][20], no studies have yet addressed the systematic influence of nanoHA on alginate-based hydrogel systems, neither the effect of distinct nanoHA amounts on its physic-chemical properties and biological response.…”
Section: Introductionmentioning
confidence: 99%